2019
DOI: 10.1016/j.jclepro.2019.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Innovation-driven industrial green development: The moderating role of regional factors

Abstract: Industrial green development (IGD) is a critical response to the over-consumption of natural resources and pollution caused by modern industry. Innovation-driven IGD has generated great interest in recent years. However, relatively less attention has been paid to the various aspects of IGD and the moderating role of regional factors, including the developmental stage of IGD, governmentscale, and enterprise-scale. The present study was conducted to fill these research gaps using panel data across 30 provinces i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 58 publications
(48 reference statements)
2
53
0
Order By: Relevance
“…conducted a study on Industrial Green Development of China, which indirectly verified the results of previous scholars [46]. Secondly, enterprises could optimize resource allocation through improving energy efficiency, and then cost-effective and efficient technical response can achieve better emission reduction [47]. Zhang et al (2017) proved the above viewpoints and found that energy efficiency has a significant impact on CO 2 emission reduction in China [48].…”
Section: Environmental Regulation Technological Innovation and Carbomentioning
confidence: 74%
“…conducted a study on Industrial Green Development of China, which indirectly verified the results of previous scholars [46]. Secondly, enterprises could optimize resource allocation through improving energy efficiency, and then cost-effective and efficient technical response can achieve better emission reduction [47]. Zhang et al (2017) proved the above viewpoints and found that energy efficiency has a significant impact on CO 2 emission reduction in China [48].…”
Section: Environmental Regulation Technological Innovation and Carbomentioning
confidence: 74%
“…Moreover, it can be found that with the increase of the network scale, cloud manufacturing enterprises that emerge in the network are dissatisfied because of the default behaviour of their partners in the process of cooperation strategy selection, which urges them to change their partners and changes the network structure, reduces the speed of network evolution and prolongs the network evolution time. Figure 9 shows the change of the network cooperation density ( 2,4,6) of the green innovation network of cloud manufacturing enterprises under different network scales and types of government punishment ( ). According to the figure, the network evolution speed when the government default penalty is 3 is significantly faster than the network evolution speed when the default penalty is 1, and with an increase in government punishment, the network cooperation density gradually increases.…”
Section: Discussionmentioning
confidence: 99%
“…With the increasingly serious problems of global warming, environmental pollution and resource depletion, various regions have experienced different degrees of public environmental pollution problems, which have become the management focus of local governments, and green economics has also become a focus of academic attention [1]. The "Made in China 2025" directive issued by the State Council of China puts forward a development policy of "innovation-driven green development" that emphasizes the important position of the green economy [2]. Meanwhile, with the rapid development of information technology and "industry 4.0", the world has increasingly implemented Internet-based economic strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, in the midstream production stage, energy consumption, and waste gas emissions can be reduced by adopting advanced technologies in clean coal utilization system along with combined heat and power system. finally, in the downstream disposal stage, innovation contributes to the recycling of wastes, remanufacturing of waste products, and reuse of waste heat (Li et al, 2019). It should be noted that technological innovation can give not only positive, but also negative effects on green growth.…”
Section: Introductionmentioning
confidence: 99%